Genome-wide identification and characterization profile of phosphatidy ethanolamine-binding protein family genes in carrot - Liu, Xing; Zhao, Donghang; Ou, Chenggang; Hao, Weidong; Zhao, Zhiwei; Zhuang, Feiyun (Frontiers in Genetics, 2022)
Members of the family of phosphatidylethanolamine-binding protein (PEBP) have been shown to be key regulators of the transition of plants from vegetative to reproductive phases. Here, a total of 12 PEBP proteins were identified in the carrot (Daucus carota L.) genome and classified into FT-like (4), TFL1-like (6), and MFT-like (2) subfamilies, that had different lengths (110-267 aa) and were distributed unevenly across seven chromosomes. Moreover, 13 and 31 PEBP proteins were identified in other two Apiaceae species, celery (Apium graveolens L.) and coriander (Coriandrum sativum L.). The phylogenetic and evolutionary results of these PEBP family proteins were obtained based on the protein sequences. In the three Apiaceae species, purifying selection was the main evolutionary force, and WGD, segmental duplication, and dispersed duplication have played key roles in the PEBP family expansion. The expression analysis showed that carrot PEBP genes exhibited relatively broad expression patterns across various tissues. In the period of bolting to flowering, the carrot FT-like subfamily genes were upregulated as positive regulators, and TFL1-like subfamily genes remained at lower expression levels as inhibitors. More interestingly, the members of carrot FT-like genes had different temporal-spatial expression characteristics, suggesting that they have different regulatory functions in the carrot reproductive phase. In summary, this study contributes to our understanding of the PEBP family proteins and provides a foundation for exploring the mechanism of carrot bolting and flowering for the breeding of cultivars with bolting resistance.